1970
DOI: 10.1161/01.res.27.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Redistribution of Cardiac Output during Hemorrhage in the Unanesthetized Monkey

Abstract: Regional flow measurements were made, using the Rudolph and Heymann microsphere technique, before and after 10, 30, and 50% of the previously measured blood volume was withdrawn from five unanesthetized rhesus monkeys restrained in horizontally tilted primate chairs. Measurements at similar time intervals were also made in seven control monkeys. Systemic arterial and central venous pressures, cardiac output, stroke volume, and hematocrit decreased progressively at each level of bleeding. Heart rate (until seve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1
2

Year Published

1974
1974
2015
2015

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 89 publications
(37 citation statements)
references
References 32 publications
3
31
1
2
Order By: Relevance
“…There are several possible explanations for the discrepancy between the conclusion of previous investigations, indicating intense renal vasoconstriction with hemorrhage (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and those in the present one, demonstrating sparing of the renal bed. Three important features of the present investigation were (a) renal blood flow was measured in the conscious animal, (b) these measurements were instantaneous and continuous, and (c) hemorrhage was not severe or prolonged, i.e., hemorrhagic shock did not develop.…”
Section: Renal Vasodilation With Hemorrhage 231contrasting
confidence: 99%
See 1 more Smart Citation
“…There are several possible explanations for the discrepancy between the conclusion of previous investigations, indicating intense renal vasoconstriction with hemorrhage (18)(19)(20)(21)(22)(23)(24)(25)(26)(27), and those in the present one, demonstrating sparing of the renal bed. Three important features of the present investigation were (a) renal blood flow was measured in the conscious animal, (b) these measurements were instantaneous and continuous, and (c) hemorrhage was not severe or prolonged, i.e., hemorrhagic shock did not develop.…”
Section: Renal Vasodilation With Hemorrhage 231contrasting
confidence: 99%
“…While measurements were recorded continuously during hemorrhage, two points were chosen to compare with control values; the first occurred before a reduction in arterial pressure, which occurred after 14±2 ml/kg of hemorrhage and is designated as the mild nonhypotensive hemorrhage response, while the second point was chosen after a sustained [20][21][22][23][24][25][26][27][28][29][30] ied hypoten-iliac flow had fallen by 58±5% to 46±4 ml/min and iliac resistance had risen from 0.88+0.05 to 1.72±0.11 -onary blood mm Hg/ml/min. These changes were all significant and transi-(P < 0.01) ( %) resistances were significantly less than without blockade (P < 0.01).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, canine cutaneous blood flow was augmented in accordance with a blood pressure elevation evoked by the carotid reflex (BOND and GREEN, 1969), but on this occasion no constriction of the cutaneous vessels was obtained. In hemorrhaging, however, constriction of cutaneous vessels was observed (NEUTZE et al, 1968 ;FORSYTH et al, 1970;SCHWINGHAMER et al, 1970). IRIKI et al (1971) reported an augmentation of cutaneous and visceral sympathetic activity in a severe hypoxia.…”
Section: Discussionmentioning
confidence: 99%
“…Bloodflow to respiratory muscles. Blood flow per gram to each of the various respiratory muscles was measured by a radioactive microsphere technique described in detail previously (9)(10)(11)(12). The modifications, validity, and reproducibility of this technique for measuring respiratory muscle blood flows were described in a previous communication (5).…”
Section: Introductionmentioning
confidence: 99%